Motorcycle Tilt Warning Sensor Using Arduino and SCA60C: Sensor Peringatan Kemiringan Sepeda Motor Menggunakan Arduino dan SCA60C - Annuur Sulaeman Iman; Akhmad Ahfas, ST., M.Kom (Indonesian Journal of Innovation Studies, 2025)
General Background: Traffic accidents involving two-wheeled motor vehicles remain a major concern in road safety due to the limited safety systems available on motorcycles. Specific Background: Sharp turns and excessive vehicle tilt angles during maneuvering can increase the risk of losing control while riding. Knowledge Gap: Existing motorcycle safety studies have discussed accident prevention systems, yet practical tilt warning devices using real-time tilt detection for rider awareness are still limited. Aims: This study aimed to design and develop a motorcycle tilt warning sensor device using an Arduino Nano and Axis Module SCA60C to provide early warnings during hazardous riding conditions. Results: The developed system successfully detected motorcycle tilt angles and activated LED and buzzer warnings at predetermined tilt ranges of 10°–45° and 145°–170°. Testing results showed differences between manual sensor measurements and motorcycle-mounted measurements ranging from 1°–20° on the left side and 1°–15° on the right side due to variations in the vehicle’s pivot point. Novelty: This research presents a tilt warning system integrating the SCA60C sensor with Arduino-based notification outputs specifically designed for motorcycle maneuver monitoring. Implications: The proposed device can support rider awareness during cornering and may contribute to reducing motorcycle accident risks through early tilt angle warnings.Highlights: Real-time angle detection activated visual and audio alerts during hazardous maneuvers. Mounted measurements produced calibration differences caused by motorcycle pivot positioning. Integrated microcontroller architecture supported continuous monitoring during cornering. Keywords: Arduino Nano; Motorcycle Safety; Tilt Warning Sensor; SCA60C Sensor; Traffic Accident Prevention